Pengaruh Kompetensi Guru Al Quran Hadis terhadap Hasil Belajar Peserta Didik di MTsS Madinatun Najah Rengat - Hawa Reskia; Risnawati Risnawati (PT. Pusmedia Group Indonesia, 2026)
This study examines the influence of Al Quran Hadis teacher competence on student learning outcomes at MTsS Madinatun Najah Rengat. Teacher competence is treated as a professional capacity that includes pedagogical, professional, social, and personal dimensions. The study used a quantitative correlational design with simple linear regression. The research participants were 30 students selected through purposive sampling. Data were collected through questionnaires, documentation of Al Quran Hadis scores, and classroom observation. Descriptive statistics, normality testing, linearity testing, Pearson correlation, ANOVA, t testing, and coefficient of determination were used to analyze the data. The normality test showed that the data were normally distributed, and the linearity test confirmed a linear relationship between teacher competence and student learning outcomes. The Pearson correlation value was 0.440 with a significance value of 0.015, indicating a moderate positive relationship. The regression model produced the equation Y = 55.280 + 0.646X. The R Square value was 0.194, meaning that teacher competence explained 19.4 percent of the variation in student learning outcomes. These findings show that Al Quran Hadis teacher competence has a positive and significant effect on learning outcomes, while other learning factors remain important for further study.